A new member of the protein kinase C family, nPKC theta, predominantly expressed in skeletal muscle. - Osada, S (1992)
A new protein kinase C (PKC)-related cDNA with unique tissue distribution has been isolated and characterized. This cDNA encodes a protein, nPKC theta, which consists of 707 amino acid residues and showed the highest sequence similarity to nPKC delta (67.0% in total). nPKC theta has a zinc-finger-like cysteine-rich sequence (C1 region) and a protein kinase domain sequence (C3 region), both of which are common in all PKC family members. However, nPKC theta lacks a putative Ca2+ binding region (C2 region) that is seen only in the conventional PKC subfamily (cPKC alpha, -beta I, -beta II, and -gamma) but not in the novel PKC subfamily (nPKC delta, -epsilon, -zeta, and -eta). Northern (RNA) blot analyses revealed that the mRNA for nPKC theta is expressed predominantly in skeletal muscle. Furthermore, nPKC theta mRNA is the most abundantly expressed PKC isoform in skeletal muscle among the nine PKC family members. nPKC theta expressed in COS1 cells serves as a phorbol ester receptor. By the use of an antipeptide antibody specific to the D2-D3 region of the nPKC theta sequence, nPKC theta was recognized as a 79-kDa protein upon sodium dodecyl sulfate-polyacrylamide gel electrophoresis in mouse skeletal muscle extract and also in an extract from COS1 cells transfected with an nPKC theta cDNA expression plasmid. Autophosphorylation of immunoprecipitated nPKC theta was observed; it was enhanced by phosphatidylserine and 12-O-tetradecanoylphorbol-13-acetate but attenuated by the addition of Ca2+. These results clearly demonstrate that nPKC theta should be considered a member of the PKC family of proteins that play crucial roles in the signal transduction pathway.